Proteomic Responses Under Cold Stress Reveal Unique Cold Tolerance Mechanisms in the Pacific White Shrimp (Litopenaeus vannamei) - Peng, Jin-Xia; He, Ping-Ping; Wei, Pin-Yuan; Zhang, Bin; Zhao, Yong-Zhen; Li, Qiang-Yong; Chen, Xiu-Li; Peng, Min; Zeng, Di-Gang; Yang, Chun-Ling; Chen, Xiaohan (Frontiers in Physiology, 2018)
The Pacific white shrimp (Litopenaeus vannamei), one of the most widely cultured shrimp species in the world, is often suffered from cold stress. In order to reveal the molecular mechanism of cold tolerance in the Pacific white shrimp, we conducted a proteomic analysis on two contrasting shrimp cultivars, namely, cold-tolerant Guihai2 (GH2) and cold-sensitive Guihai1 (GH1) under normal temperature 28°C, cold stress 16°C, and 16°C recovered to 28°C, respectively. In total, 3,349 proteins were identified, among which 2,736 proteins were quantified. Based on GO annotation, the main differentially expressed proteins were belonged to biological process, cellular component and molecular function. KEGG pathway annotation found that the main changes were in lysosome, ribosome, and oxidative phosphorylation, etc. Subcellular Localization analysis showed significant changes present in cytosol, extracellular and mitochondria, etc. Combining the enrichment-based clustering analysis and qRT-PCR analysis, we found that glutathione S-transferase, zinc proteinase, m7GpppX diphosphatase, AP2 transcription complex, and Zinc-finger transcription factors played a major role in cold stress response in the Pacific white shrimp. Moreover, structure proteins including different types of lectin and DAPPUDRAFT were indispensable for cold stress tolerance in the Pacific white shrimp. These results indicated molecular mechanism of Pacific white shrimp in response to cold stress and provided a new insight in breeding new cultivars with cold tolerance.